Molecular Profiling of Selected Cassava (Manihot esculenta Crantz) Germplasm Using ISSR and SSR Markers - K. I., Asha; Ann Maria, Varghese; N., Krishna Radhika; A. V. V., Koundinya; B. S., Prakash Krishnan (JOURNAL OF ROOT CROPS, 2020)
Root and tuber crops are those plant species that store their food inside their stem or root. They are the staple food for many people in developing countries and also a global source of carbohydrate. Cassava (Manihot esculenta Crantz) is a root crop belonging to section Fructicosae, family Euphorbiaceae and of class Dicotyledons. Cassava is a typical diploid species with chromosome number as 2n=36. Molecular markers have proved to be valuable tools in the characterization and evaluation of genetic diversity within and between species and populations. Inter simple sequence repeat (ISSR) and simple sequence repeat (SSR) markers provide more sophisticated analysis of genetic diversity, cultivar identification, population genetic structure and other events of evolutionary biology processes. In the present study, the genetic variability among 14 indigenous accessions of cassava germplasm maintained in the field genebank of ICAR-CTCRI was estimated by molecular characterization using six ISSR and nine SSR markers. DNA was extracted from young fresh leaves of cassava using the CTAB method. The genetic distances based on ISSR markers ranged from 0.102941 to 0.231083. Among the 14 cassava accessions, the lowest genetic distance (0.102941) was observed between CI-3 and CI-2 for the 6 ISSR markers and the genetic distances based on SSR markers ranged from 0.00 to 0.283507. The lowest genetic distance (0.00) was observed between CI-3 and CI-2 suggesting that these two genotypes are similar for 9 SSR markers. The value of expected heterozygocity ranged from 0.92 (UBC 807) to 0.98 (UBC 808, UBC 817, UBC 836) and from 0.00 (SSRY 102) to 0.97 (SSRY 45, SSRY 100). The Polymorphism Information Content values ranged from 0.133 (UBC 808, UBC 836) to 0.180 (UBC 845) and from 0.000 (SSRY 102) to 0.500 (SSRY 9, SSRY 147, SSRY 148, SSRY 161) indicating the low to moderate polymorphism for these alleles.The study revealed that only two accessions (CI-161 and CI-296) exhibit 100% similarity by molecular characterization using 6 ISSR and 9 SSR markers among the 14 accessions grouped under a single core group morphologically. Hence, it is concluded that the molecular markers used in the present study can very effectively be used as tools in future for germplasm characterization, variability studies, core collection development and also diversity studies in cassava.